Influence of Brand Image and Islamic Values on Patient Loyalty in YARSI Hospital in Jakarta, Indonesia - Dede Yunus; Rifqatussa'adah; Yudi Amiarno; Dicky Budiman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Patient loyalty has become a critical challenge for hospitals operating in an increasingly competitive healthcare environment, particularly for faith-based institutions that integrate religious principles into service delivery. Islamic hospitals, such as YARSI Hospital in Jakarta, must not only maintain high service quality but also ensure that Islamic values are meaningfully embedded in patient care. However, empirical evidence examining how brand image and Islamic values interact with patient experience and satisfaction to influence patient loyalty remains limited. This study aims to analyze the direct influence of brand image, Islamic values, patient experience, and patient satisfaction on patient loyalty at YARSI Hospital. A mixed-methods approach with a concurrent triangulation design was employed to obtain comprehensive insights. Quantitative data were collected through structured questionnaires administered to 388 outpatients, measuring perceptions of brand image, Islamic values integration, patient experience, satisfaction, and loyalty. Multiple linear regression analysis was used to assess the relationships among variables. Qualitative data were obtained through in-depth interviews with selected patients to enrich and contextualize the quantitative findings, and thematic analysis was applied. The results demonstrate that all examined variables significantly and positively influence patient loyalty (p < 0.05). Patient satisfaction emerged as the strongest predictor of loyalty (β = 0.440), followed by brand image (β = 0.287), Islamic values (β = 0.238), and patient experience (β = 0.209). Qualitative findings corroborated these results, highlighting that the integration of Islamic values provides spiritual reassurance and strengthens emotional bonds between patients and the hospital. In conclusion, patient loyalty in Islamic healthcare settings is shaped by a combination of service quality, value congruence, and positive patient experiences. Strengthening brand image, consistently integrating Islamic values, and enhancing patient satisfaction are essential strategic priorities for sustaining patient loyalty in faith-based hospitals.